Anteroposterior Patterning of Gene Expression in the Human Infant Sclera: Chondrogenic Potential and Wnt Signaling. (2nd January 2017) - Seko, Yuko; Azuma, Noriyuki; Yokoi, Tadashi; Kami, Daisuke; Ishii, Ryuga; Nishina, Sachiko; Toyoda, Masashi; Shimokawa, Hitoyata; Umezawa, Akihiro
ABSTRACT: Purpose/Aim : We sought to identify the anteroposterior spatial gene expression hierarchy in the human sclera to develop a hypothesis for axial elongation and deformity of the eyeball. Materials and Methods : We analyzed the global gene expression of human scleral cells derived from distinct parts of the human infant sclera obtained from surgically enucleated eyes with retinoblastoma, using Affymetrix GeneChip oligonucleotide arrays, and compared, in particular, gene expression levels between the anterior and posterior parts of the sclera. The ages of three donors were 10M, 4M, and 1Y9M. Results : K-means clustering analysis of gene expression revealed that expression levels of cartilage-associated genes such as COLXIA and ACAN increased from the anterior to the posterior part of the sclera. Microarray analyses and RT-PCR data showed that the expression levels of MGP, COLXIA, BMP4, and RARB were significantly higher in the posterior than in the anterior sclera of two independent infant eyes. Conversely, expression levels of WNT2, DKK2, GREM1, and HOXB2 were significantly higher in the anterior sclera. Among several Wnt-family genes examined, WNT2B was found to be expressed at a significantly higher level in the posterior sclera, and the reverse order was observed for WNT2 . The results of luciferase reporter assays suggested that a GSK-3β inhibitor stimulated Wnt/β-catenin signaling particularly strongly in the posterior sclera. The expression pattern of RARB, a myopia-related gene, was similar in three independent eyes. Conclusions : Chondrogenic potential was higher and Wnt/β-catenin signaling was more potently activated by a GSK-3β inhibitor in the posterior than in the anterior part of the human infant sclera. Although the differences in the gene expression profiles between the anterior and posterior sclera might be involved only in normal growth processes, this anteroposterior hierarchy in the sclera might contribute to disorders involving abnormal elongation and deformity of the eyeball, including myopia.